The Influence of Work Ability and Motivation toward Social Escort’s Performance on Family Hope Program (FHP) - Hartono, Uji (Jurnal Penelitian Kesejahteraan Sosial, 2018)
The research aims to know the influence of the work ability towards social escort’s performance of FHP. The influence of work motivation towards social escort’s performance of FHP. The influence between the work ability and work motivation jointly on the work performance of social escorts of PKH. The subjects of the research were 39 people. The technique of colleting data used questionares, interviews, and documentary analysis. The analysis of the data used statistical program SPSS regression technique.The results showed that the effect of working ability (X1) on the work performance (Y) with a regression coefficient of 0.326. The effect of work motivation (X2) on the work performance (Y) was significant with a regression coefficient of 0.557. The effect of jointly working ability and work motivation (X1 and X2) on the work performance (Y) with the coefficient of determination (R2) of 77.2 percent. Based on the analysis that the ability to work (X1) had significant influence on the work performance (Y), the first hypothesis was accepted. The analysis of the second hypothesis that motivation (X2) has a significant influence, so that the second hypothesis was accepted. The analysis of the third hypothesis that the ability to work (X1) and motivation (X2) has significant influence jointly on the performance (Y), so that the third hypothesis was accepted. The recommendation that was to improve the ability and motivation of social escort of FHP through training and technical assistance so that its performance gradually increased.